A Non-specific Setaria italica Lipid Transfer Protein Gene Plays a Critical Role under Abiotic Stress - Pan, Yanlin; Li, Jianrui; Jiao, Licong; Li, Cong; Zhu, Dengyun; Yu, Jingjuan (Frontiers in Plant Science, 2016)
Lipid transfer proteins (LTPs) are a class of cysteine-rich soluble proteins having small molecular weights. LTPs participate in flower and seed development, cuticular wax deposition, also play important roles in pathogen and abiotic stress responses. A nonspecific LTP gene (SiLTP) was isolated from a foxtail millet (Setaria italica) suppression subtractive hybridization (SSH) library enriched for differentially expressed genes after abiotic stress treatments. A semi-quantitative reverse transcriptase PCR analysis showed that SiLTP was expressed in all foxtail millet tissues. Additionally, the SiLTP promoter drove GUS expression in root tips, stems, leaves, flowers and siliques of transgenic Arabidopsis. Quantitative real-time PCR indicated that the SiLTP expression was induced by NaCl, polyethylene glycol and abscisic acid. SiLTP was localized in the cytoplasm of tobacco leaf epidermal cells and maize protoplasts. The ectopic expression of SiLTP in tobacco resulted in higher levels of salt and drought tolerance than in the wild type (WT). To further assess the function of SiLTP, SiLTP overexpression (OE) and RNA interference (RNAi)-based transgenic foxtail millet were obtained. SiLTP-OE lines performed better under salt and drought stresses compared with WT plants. In contrast, the RNAi lines were much more sensitive to salt and drought compared than WT. Electrophoretic mobility shift assays and yeast one-hybrids indicated that the transcription factor (TF) ABA-responsive DRE-binding protein (SiARDP) could bind to the dehydration-responsive element of SiLTP promoter in vitro and in vivo, respectively. Moreover, the SiLTP expression levels were higher in SiARDP-OE plants compared than the WT. These results confirmed that SiLTP plays important roles in improving salt and drought stress tolerance of foxtail millet, and may partly be up-regulated by SiARDP. SiLTP may provide an effective genetic resource for molecular breeding in crops to enhance salt and drought tolerance levels.